The Importance of Ethnicity: Developing a Measure of Minority Ethnic Value and Value-Expressive Behavior Among Chinese Ethnic Minorities - Yang, Yanli; Liang, Fangmei; Quan, Fangying; Jiang, Guangyu; Yu, Ke; Zheng, Yong (Frontiers in Psychology, 2019)
In this study we developed the Chinese Minority Ethnic Value Questionnaire (CMEVQ) and the Chinese Minority Ethnic Value-Expressive Behavior Questionnaire (CMEVEBQ) to assess the importance of ethnicity from the standpoint of diverse ethnic values and behavioral manifestations. Drawing on self-construal theory, social identity theory, and value theory, we conducted a review of literature, in-depth interviews, semi-structured questionnaires, and expert reviews. A total of 18 items for the CMEVQ and CMEVEBQ were developed. Data were collected from three samples of Chinese ethnic minorities (mainly college students). We generated two sets of item pools from the pilot sample (n = 438). Then we examined the dimensions and final items of the CMEVQ and CMEVEBQ using exploratory factor analysis (EFA) with sample 1 (n = 665). After that, we conducted a confirmatory factor analysis (CFA) to recheck the factor structure of two refined, mutually matched, yet independent scales obtained from Study 1 with sample 2 (n = 1309); meanwhile criterion-related, K-means cluster, t-tests, and multiple regression analyses were used to test the validity of and relationship between the CMEVQ and CMEVEBQ. Results showed that the multidimensional constructs with six shared first-order factors (Minority Ethnic Consciousness, Exploration, Involvement, Alienation, Inheritance, and Mastery) demonstrated a better fit for the data and supported the conceptual framework. Both questionnaires demonstrated adequate internal consistency reliability, convergent and discriminant validity, and ecological validity. That is, as practical, psychometrically sound measures, the CMEVQ and CMEVEBQ can be used to measure the importance of ethnicity for Chinese ethnic minorities. They also extend the content and sample fields of value research.